A Sociopragmatic Analysis Of Directive Utterances Used In Letters To Juliet Movie Script - Pramesti, Maya Hangga, Drs. Sigit Haryanto, M.Hum, Dra. Dwi Haryanti, M.Hum (2013)
The objectives of the study are to classify the language form and describe speaker‟s intention and the politeness pattern of directive utterance in Letters to Juliet Movie Script. The type of this research is descriptive qualitative. The object of the research is directive utterances in Letters to Juliet movie script. The source of data is Letters to Juliet movie script. In collecting the data the writer uses documentation method by selecting the directive utterance which can be found in Letters To Juliet Movie Script. This movie written by Jose Rivera. This research employs the theory of language form, speech act and Face Threatening Act Theory. The results of the study show that first, the language forms of directive utterances are: declarative sentence, interrogative and imperative sentence. There are 13 data of declarative sentences, 5 data of interrogative sentences, and 12 data of imperative sentences. Second, the speaker‟s intentions of using directive utterance are: commanding, requesting, suggesting, warning and permitting. There are 10 data of commanding, 12 data of requesting, 5 data of suggesting, 2 data of warning, and 1 datum of permitting. Third, the writer finds 9 data of Bald on Record, 13 data of Positive Politeness, 6 data of Negative Politeness, and 2 data of Off Record Strategy.